Morning Routine Activities Based on Pancasila Literacy to Instill Nationalist Character in Elementary School Students - Moch. In’am Ansori; Badruli Martati; Lilik Binti Mirnawati (Literasi Nusantara, 2026)
This study aims to describe Pancasila Literacy-Based Morning Habituation Activities to Instill Nationalist Character in Elementary Schools. This study uses a Quantitative method. The subject I used in this study was students in grades 5-6 of Mi Al-Mustofa in Surabaya, the data collection techniques used were post test and pre test one group observation, interview, and documentation. Data analysis uses the Pearson and Kuder Richardson Correlation Technique, which shows that Pancasila literacy-based morning activities are not only to fill the hours of social work in the morning but will also have an effect on instilling a Nationalist character.